The Use of Domino Card Media in Arabic Language Learning to Improve Qawā'id Understanding - Nada Najwa, Dewi Qotrun; Suparmanto, Suparmanto; Raeza, Nadia; Rizki Umar, Azidan (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2023)
This research aims to evaluate the effectiveness of using domino media in improving the understanding of qawā'id (fundamental principles) in Arabic language learning at MA Al-Raisiyah Sekarbela. This research was conducted on May 24, 2023/2024 academic year involving 21 class XI students. The research uses descriptive qualitative methods. The research results show that using domino learning media positively increases students' understanding of qawā'id in learning Arabic at MA Al-Raisiyah Sekarbela. This learning media has the potential to facilitate the learning process and increase student involvement in understanding qawā'id material. Preliminary findings indicate that the use of domino media has a positive influence on students' qawā'id understanding. It promotes engagement, interactivity, and a practical approach to learning, which is particularly beneficial for comprehending the intricate rules of the Arabic language. Additionally, students express enthusiasm for this novel approach and report increased motivation and confidence in applying qawā'id principles. This research contributes to the growing literature on innovative teaching methodologies and technology-enhanced Learning in Arabic language education. The results suggest that integrating domino media into the curriculum can lead to more effective qawā'id acquisition, ultimately enhancing Arabic language proficiency. The findings have implications for Arabic language educators and curriculum developers seeking to improve the quality of instruction and learning outcomes in qawā'id comprehension.